2012
DOI: 10.1093/nar/gks272
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary and genetic analyses of mitochondrial translation initiation factors identify the missing mitochondrial IF3 in S. cerevisiae

Abstract: Mitochondrial translation is essentially bacteria-like, reflecting the bacterial endosymbiotic ancestry of the eukaryotic organelle. However, unlike the translation system of its bacterial ancestors, mitochondrial translation is limited to just a few mRNAs, mainly coding for components of the respiratory complex. The classical bacterial initiation factors (IFs) IF1, IF2 and IF3 are universal in bacteria, but only IF2 is universal in mitochondria (mIF2). We analyse the distribution of mitochondrial translation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
61
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(66 citation statements)
references
References 91 publications
5
61
0
Order By: Relevance
“…E. coli complementation experiments have demonstrated that expression of plasmid-borne bovine mIF2, but not E. coli IF2 can support the viability of an E. coli strain lacking genomic copies of initiation factors IF2 and IF1 [27]. This result was interpreted in a model postulating that, despite a lack of homology to IF1 and twice smaller size [9], the insertion serves as a functional replacement of IF1. Subsequent structural studies demonstrated that the insertion shares the same binding pocket on the bacterial ribosome as IF1 [26], seemingly supporting the idea that it has evolved as an IF1 substitute.…”
Section: Mitochondrial Initiation Factor 2 (Mif2)mentioning
confidence: 99%
“…E. coli complementation experiments have demonstrated that expression of plasmid-borne bovine mIF2, but not E. coli IF2 can support the viability of an E. coli strain lacking genomic copies of initiation factors IF2 and IF1 [27]. This result was interpreted in a model postulating that, despite a lack of homology to IF1 and twice smaller size [9], the insertion serves as a functional replacement of IF1. Subsequent structural studies demonstrated that the insertion shares the same binding pocket on the bacterial ribosome as IF1 [26], seemingly supporting the idea that it has evolved as an IF1 substitute.…”
Section: Mitochondrial Initiation Factor 2 (Mif2)mentioning
confidence: 99%
“…Mitochondrial mRNAs lack Shine-Dalgarno elements that could facilitate their interaction with ribosomes, and it is unclear how translation initiation is accomplished. Mitochondria have homologs of bacterial initiation factors IF2 (the functional equivalent of bacterial IF1 and IF2 [27]) and IF3 [28–32]. In mammals, IF2-mt promotes the binding of the initiator formylmethionine-tRNA (fMet-tRNA) to the AUG codon at the ribosomal peptidyl-site [33].…”
Section: Introductionmentioning
confidence: 99%
“…Both IF3 and IF2 are also responsible for the fidelity of decoding the initiation AUG by fMet-tRNA Met f at the P site of 30S subunits (10). IF1 is universal (11) and essential for viability (12). It is the smallest factor, with 72 amino acid residues in Escherichia coli, and binds to the decoding center at the ribosomal A site (13).…”
mentioning
confidence: 99%